MENINGKATKAN MOTIVASI BELAJAR DENGAN PENGGUNAAN ALAT PERAGA MATA PELAJARAN SENI BUDAYA PADA SISWA KELAS VIII-1 SMP NEGERI 2 TANJUNG MORAWA - Hairani, Tuti (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2016)
Based on research report indicates that first period, a condition of using audio visual aid which is done by teacher gets mark B. It means included into a good category, mean while students learning motivation at first period is categorized in getting the best mark merely on indicator. It is enough in a total 7 indicators, it is less a total 7 indicator and it is the least a total 3 indicator. It is averageÂ in count at first period namely 66,95 of 36 students or merely get good category. Mean while in second period a condition in using audio visual aids that is done by teacher getting mark A. It means that included into the best category. The case undergoes the most significational progess, while motivation of students learning in second period got a lot of changes. Key Word : Motivation, audio visual aids.